“O picadeiro é encantado”: tempo, festa e narrativas etnobiográficas de um palhaço de circo - Gouveia, Ethel de Paula (2023)
This thesis has as its central core the creation of an ethnobiography regarding the most longstanding active circus clown in Ceará: José de Abreu Brasil, Pimenta the clown. He is an artist who embodies the local circus scene and is an exemplary case from a methodological point of view. Pimenta, seventy years old, describes himself as a traditional circus performer and is the protagonist of a small circus touring the neighborhoods of the outskirts of Fortaleza, his "walking toy". As a parameter for understanding cultural facts and seeking to access a panorama of the social history of circus and circus culture, this itinerant comedian is examined here as a craftsman of himself, as well as of places, "webs" and "threads" of vital entanglements that form the circus-mesh (Ingold, 2015). Pimenta is, as such, the guiding character through which we tap into five small itinerant circuses of the canvas circulating in the outskirts of Fortaleza, giving way to traditional memories and narratives "of the canvas" that cross and illuminate his biography. Rooted in the notion of participative observation and applying semi-structured interviews as both a means of coming closer to and examining the ways of life and work of circus families and artists, this thesis also set out to create memory as a political gesture of a present-day action. To this end, we sought to go beyond the idealized reference to the "magical" world of the circus to shed light on the "tactics" and "cunning" (De Certeau, 2009) that allow for "living together" or a "practice of cooperation" (Sennett, 2012), recognizing the artistic universe as a space of individual and social commitment. Beyond playfulness and comicality, we find that the circus acts as a time machine, balancing dishes between multiple temporalities, rallying a range of surviving gestures and words, shaking socially agreed cultural norms and values, stubbornly following traces of the childhood of language, of the animality present in humans, of the laughter that slips out as an expression of joy and pain. Therein lie a few glimpses of the inalienable adventure of the clown, of the thesis and of a researcher-narrator who is also a craftsman and bricoleur that, like a circus, is continuously shaped by the temperature of its encounters.